If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 1) + 3(7 + -6x) = 16x Reorder the terms: 9(1 + x) + 3(7 + -6x) = 16x (1 * 9 + x * 9) + 3(7 + -6x) = 16x (9 + 9x) + 3(7 + -6x) = 16x 9 + 9x + (7 * 3 + -6x * 3) = 16x 9 + 9x + (21 + -18x) = 16x Reorder the terms: 9 + 21 + 9x + -18x = 16x Combine like terms: 9 + 21 = 30 30 + 9x + -18x = 16x Combine like terms: 9x + -18x = -9x 30 + -9x = 16x Solving 30 + -9x = 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 30 + -9x + -16x = 16x + -16x Combine like terms: -9x + -16x = -25x 30 + -25x = 16x + -16x Combine like terms: 16x + -16x = 0 30 + -25x = 0 Add '-30' to each side of the equation. 30 + -30 + -25x = 0 + -30 Combine like terms: 30 + -30 = 0 0 + -25x = 0 + -30 -25x = 0 + -30 Combine like terms: 0 + -30 = -30 -25x = -30 Divide each side by '-25'. x = 1.2 Simplifying x = 1.2
| 13y-8y-4=56.20 | | 0=-.25x+6 | | x-0.6=0.4 | | 4y+-3y-6=1 | | 3x-7=10-2x | | 6x+3=8x-11 | | r+(-29)=-38 | | x-1/4=1/8 | | 3(2+x)=0 | | 7d+5d+4d-4= | | x^2-3x+1-x^2+2x+7= | | 2(x-3)-4x=-10 | | -4(9+z)=-52 | | 5b=75 | | x-0.9=0.3 | | f(x)=3(x-2)+7 | | 2a+2=a-10 | | 6y+-2y-7=9 | | 9+8x=-5+x | | 2z+-2z+4=4 | | 7(9+z)=91 | | px(q+5)= | | x+1.2=0.6 | | 9z+7z-5=43 | | 4z+-3z+2=-2 | | p+7=-2 | | y=-5+-15 | | 5x-x-7=29 | | 100x=5580 | | -4(-5+x)=4 | | ln(y)=4 | | 3t^2-2t-1=5 |